Electrical field dependent mobility analysis of ultralong individual single walled carbon nanotube field-effect transistor - Krishna, S. V. Hari (2014)
Ethanol based chemical vapour deposition (CVD) was used to grow clean individual ultralong single walled carbon nanotubes (SWCNTs) and fabricated as carbon nanotube field-effect transistors (CNTFETs). Here, the two kinds of mobility-effective physical mobility and conventional field-effect mobility were investigated using classical diffusive metal-oxide-semiconductor field-effect transistor (MOSFET) model and their ratios were analysed in the strong inversion region and the near-threshold region as a function of the vertical gate bias and horizontal drain bias. The fabricated CNTFETs showed intrinsic mobilities as high as 105 cm2 V–1 s–1 and device mobility greater than 104 cm2 V–1 s–1 consistently at room temperature 300 K. In the linear regime, the ratio of both the above mobilities obtained for a number of devices in the strong inversion and near–threshold region were around to have mean values of 2.34 and 10.18 respectively. The transport is diffusive and scattering dominated, which could pave way for mobility based nanosensing for future applications.